Return Strategies of Competing E-Sellers: Return Freight Insurance vs. Return Pickup Services - Qiyuan Li; Yanli Fang; Yan Chen (Mathematics)
Over the past decade, return freight insurance (RFI) and return pickup services (RPSs) have emerged as dominant return service strategies in e-commerce, particularly in China’s competitive online retail market. Despite their prominence, the strategic dynamics guiding e-sellers’ choice between these services remain underexplored. This study develops a game-theoretic model to analyze the equilibrium return strategies of two horizontally competing e-sellers with varying misfit probabilities. By examining four subgames, we identify the conditions under which e-sellers converge on either RFI or RPSs. Our findings revealed that highly similar or highly differentiated products typically favor RFI due to intense price competition or reduced need for service-based competition, while moderately differentiated products lead to RPS adoption as service quality becomes a key competitive lever. Additionally, competitive pressure often drives e-sellers to adopt homogenized return strategies, particularly RPSs, to maintain market position. The equilibrium outcomes are shaped by misfit probability differences, consumer hassle costs, and cost structures, offering actionable insights into optimizing return strategies in competitive e-commerce environments. These findings provide actionable insights into optimizing return service strategies in competitive e-commerce environments and contribute to the growing literature on return policies as a competitive lever in online retail markets.